The grudge [videorecording (DVD)] - Gilpin, Betty; Riseborough, Andrea, 1981-; Sadler, William, 1950-; Shaye, Lin, 1944- (Sony Pictures Home Entertainment, 2020)
After a young mother murders her family in her own house, a single mother and young detective try to investigate and solve the case. Later, she discovers the house is cursed by a vengeful ghost that dooms those who enter it with a violent death. Now, she runs to save herself and her son from demonic spirits from the cursed house in her neighborhood.